ANALISIS STUDI KASUS JUAL BELI RUMAH SUSUN BERSUBSIDI - Nayyara Putri Aliya; Saffira Aulia; Azka Tsabitah Hamzah; Athaya Rahmawati; Dwi Aryanti Ramadhani (Cahaya Ilmu Bangsa, 2024)
Analysis of the case of buying and selling subsidized flats brings attention to the point of view of the agreement in it. In the case of subsidized flats, Marunda Flats, the case entered the realm of Unlawful Acts (PMH). The research method in this article uses a type of case study because it is used in analyzing civil lawsuit cases regarding Unlawful Acts (PMH). The renter in the Marunda Flat has committed a Wrongful Act for misuse of state assets and violated the Regulation of the Minister of Public Works and Public Housing Number 14/PRT/M/2018. Strict action is needed to enforce the law and provide a deterrent effect for the perpetrators involved in the misuse of subsidized flats.